Grapevine leafroll-associated virus 3 - Maree, Hans J.; Almeida, Rodrigo P.; Bester, Rachelle; Chooi, Kar Mun; Cohen, Daniel; Dolja, Valerian V.; Fuchs, Marc F.; Golino, Deborah A.; Jooste, Anna E.; Martelli, Giovanni P.; Naidu, Rayapati A.; Rowhani, Adib; et al. (Frontiers in Microbiology, 2013)
Grapevine leafroll disease (GLD) is one of the most important grapevine viral diseases affecting grapevines worldwide. The impact on vine health, crop yield and quality is difficult to assess due to a high number of variables, but significant economic losses are consistently reported over the lifespan of a vineyard if intervention strategies are not implemented. Several viruses from the family Closteroviridae are associated with GLD. However, Grapevine leafroll-associated virus 3 (GLRaV-3), the type species for the genus Ampelovirus, is regarded as the most important causative agent. Here we provide a general overview on various aspects of GLRaV-3, with an emphasis on the latest advances in the characterization of the genome. The full genome of several isolates have recently been sequenced and annotated, revealing the existence of several genetic variants. The classification of these variants, based on their genome sequence, will be discussed and a guideline is presented to facilitate future comparative studies. The characterization of sgRNAs produced during the infection cycle of GLRaV-3 has given some insight into the replication strategy and the putative functionality of the ORFs. The latest nucleotide sequence based molecular diagnostic techniques were shown to be more sensitive than conventional serological assays and although ELISA is not as sensitive it remains valuable for high-throughput screening and complementary to molecular diagnostics. The application of next-generation sequencing is proving to be a valuable tool to study the complexity of viral infection as well as plant-pathogen interaction. Next-generation sequencing data can provide information regarding disease complexes, variants of viral species, and abundance of particular viruses. This information can be used to develop more accurate diagnostic assays. Reliable virus screening in support of robust grapevine certification programs remains the cornerstone of GLD management.